Impacts of Human Activities on Archeological Sites in Southern Egypt Using Remote Sensing and Field Data - Abdalla, Fathy; Moubark, Karem; Abdelkareem, Mohamed (2016)
The famous archaeological sites of Egypt are potentially affected due to human activities that constitute the main threats through rising of groundwater level as a result of seepage of drainage and sewage water, despite of the arid and hyper arid conditions. This area witnessed several changes during the last four decades, particuarly loss of agricultural/arable lands to residential and commercial development. The characterization and evolution of human activities were examined and discussed based on spatial and temporal analysis and interpretation of remote sensing data and field survey. Multi-temporal analysis using Principal Component Analysis (PCA), classification and Normalized difference vegetation index (NDVI) techniques were applied to a series of satellite images. Increasing population and the lack of reticulated wastewater systems allowed recharging and pollution of groundwater in the study area. The chemical analysis of the collected groundwater samples indicate that sodium chloride and sodium sulphate are the two most common destructive salts in the groundwater. Such salts were observed in the deteriorated monuments of the studied temples and foundations. The dewatering processes help in preserving the monuments from deterioration by reducing the groundwater level from 73 to 71.30 and from 73 to about 71 at Karnak and Luxor temples, respectively.
Keywords: Groundwater; Remote sensing